Autoantibodies may predict the neurological severity of patients with Wilson disease. (3rd October 2022) - Wolska, M; Eyileten, C; Nowak, A; Palejko, A; Cudna, A; Litwin, T; Antczak-Kowalska, M; Kurkowska-Jastrzebska, I; Czlonkowska, A
Abstract: Background: Wilson's disease (WD) is a rare, autosomal disorder of copper metabolism, in which antibodies mediate and modulate the clinical manifestation of the CNS disease. The aim of this study was to investigate the presence and impact of autoantibodies in the clinical course of WD. Method: Study involved 88 WD diagnosed and already treated patients with 7-years follow-up. Indirect immunofluorescence assays and Western Blot analysis was used. Results: Patients who presented neurological manifestations had significantly more frequently ANA, ANCA and ANNA presence than in healthy individuals (p=0.029, p=0.009, p=0.025, respectively). In patients treated with d-penicillamine positive ANA antibodies were observed more frequently (p=0.005), whereas in zinc sulphate treated patients PP, ANCA and ANNA were significantly more frequently positive (p=0.038, p=0.024, p=0.002, respectively). Within the group of patients who died, positive ANA antibodies were significantly more frequent in comparison to patients who survived (p=0.020). Patients presenting positive cANCA had significantly higher UWDRS II, III and total scores compared to patients without ANCA antibody (p=0.033, p=0.022, p=0.022, respectively). Conclusion: Drug-induced ANCAs may have a predictive value, as it is positively correlated with UWDRS II, III and total score in patients with WD. Only patients with neurological manifestations had significantly higher ANA, ANCA and ANNA presence. Increased positivity of those antibodies may predict the neurological manifestation of the severe cases and may be helpful for the neurological assessment of WD. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): Medical University of Warsaw